丹麦银屑病患者中的局部外用皮质类固醇的使用. (2nd January 2019) - Svendsen, M.T.; Ernst, M.S.; Andersen, K.E.; Andersen, F.; Johannessen, H.; Pottegåard, A.
Abstract : Linked Article: Svendsen et al. Br J Dermatol 2019;180 :157–164